Latin Vulgate, Esther: Liber Esther - Anonymous (Salt Lake City, UT : Project Gutenberg, 1997)
"Latin Vulgate, Esther: Liber Esther" by Anonymous is a biblical text set during the Persian Empire. When Queen Vashti defies King Ahasuerus, a young Jewish woman named Esther becomes the new queen. Her cousin Mordecai discovers a plot by the king's advisor Haman to destroy all Jews in the empire. Esther must risk everything by revealing her hidden identity to save her people from genocide, leading to an unexpected reversal of fate. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Book_of_Esther
Release date is 1997-02-01
Produced by Dennis McCarthy
Keywords: Bible. Esther